Plyometric training improves voluntary activation and strength during isometric, concentric and eccentric contractions - Behrens, M.; Mau-Moeller, A.; Mueller, K.; Heise, S.; Gube, M.; Beuster, N.; Herlyn, P. K.E.; Fischer, D.-C.; Bruhn, S. (Journal of Science and Medicine in Sport, 2016)
Objectives: This study investigated effects of plyometric training (6 weeks, 3 sessions/week) on maximum voluntary contraction (MVC) strength and neural activation of the knee extensors during isometric, concentric and eccentric contractions. Design: Twenty-seven participants were randomly assigned to the intervention or control group. Methods: Maximum voluntary torques (MVT) during the different types of contraction were measured at 110Â° knee flexion (180Â° = full extension). The interpolated twitch technique was applied at the same knee joint angle during isometric, concentric and eccentric contractions to measure voluntary activation. In addition, normalized root mean square of the EMG signal at MVT was calculated. The twitch torque signal induced by electrical nerve stimulation at rest was used to evaluate training-related changes at the muscle level. In addition, jump height in countermovement jump was measured. Results: After training, MVT increased by 20 N m (95% CI: 5-36 N m, P = 0.012), 24 N m (95% CI: 9-40 N m, P = 0.004) and 27 N m (95% CI: 7-48 N m, P = 0.013) for isometric, concentric and eccentric MVCs compared to controls, respectively. The strength enhancements were associated with increases in voluntary activation during isometric, concentric and eccentric MVCs by 7.8% (95% CI: 1.8-13.9%, P = 0.013), 7.0% (95% CI: 0.4-13.5%, P = 0.039) and 8.6% (95% CI: 3.0-14.2%, P = 0.005), respectively. Changes in the twitch torque signal of the resting muscle, induced by supramaximal electrical stimulation of the femoral nerve, were not observed, indicating no alterations at the muscle level, whereas jump height was increased. Conclusions: Given the fact that the training exercises consisted of eccentric muscle actions followed by concentric contractions, it is in particular relevant that the plyometric training increased MVC strength and neural activation of the quadriceps muscle regardless of the contraction mode.